2014
DOI: 10.4254/wjh.v6.i6.419
|View full text |Cite
|
Sign up to set email alerts
|

Management of hepatitis C virus infection in hemodialysis patients

Abstract: currently the main treatment strategies for MHD patients with active HCV replication, but how to increase the sustained virological response and decrease the side effects is the key problem. IFNα-free treatments with two or three direct-acting antivirals without ribavirin in MHD patients are waiting for future investigations. Key words: Hemodialysis; Hepatitis C virus; Epidemiology; Risk factors; Prophylaxis; Treatment Core tip: The new hepatitis C virus (HCV) infections during maintenance hemodialysis (MHD) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…aggravation of liver fibrosis (F) [1]; the risk of complications related to liver puncture biopsy (LPB) is higher, 13.2 % [1]. Prevalence is significantly correlated with the length of time on HD and the processed blood volume [6][7][8][9].…”
Section: Introductionmentioning
confidence: 97%
“…aggravation of liver fibrosis (F) [1]; the risk of complications related to liver puncture biopsy (LPB) is higher, 13.2 % [1]. Prevalence is significantly correlated with the length of time on HD and the processed blood volume [6][7][8][9].…”
Section: Introductionmentioning
confidence: 97%
“…Ribavirin (RBV) was considered to be contraindicated in hemodialysis patients because of the possible development of hemolytic anemia. 9,10 However, several studies reported the use of low-dose ribavirin in combination with interferon, carefully controlling for anemia and monitoring serum concentration of the drug during treatment in hemodialysis patients. [11][12][13] The primary goal of the antivirological treatment is eradication of the HCV infection, which is synonymous with sustained virological response (SVR).…”
Section: Introductionmentioning
confidence: 99%
“…The hemodialysis procedure requires vascular access for prolonged periods and thus put patients on long-term hemodialysis at increased risk of acquiring HCV infection [2,3]. The reported prevalence of anti-HCV or HCV infection among hemodialysis population is much higher than that of the general population [4,5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Following the implementation of appropriate precautions for infection control, the prevalence of hepatitis C had declined recently [8,17,18,19]. However, it also increased the mortality and morbidity in hemodialysis patients [8,20,21]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation